The effectiveness and safety of laparoscopic sleeve gastrectomy with different sizes of bougie calibration: A systematic review and meta-analysis. (January 2018) - Wang, Yao; Yi, Xiao-Yan; Gong, Li-lin; Li, Qi-fu; Zhang, Jun; Wang, Zhi-hong
Abstract: Objectives: This systematic review and meta-analysis was performed to compare the influence of different calibrating bougie sizes on clinical outcomes in laparoscopic sleeve gastrectomy (LSG) for patients with obesity. Materials and methods: A systematic review of the literature was performed using the key words: "laparoscopic sleeve gastrectomy", "bougie size", "calibration", "obesity", and "obese" for searches of electronic databases up to October 2017. Clinical characteristics such as, the percentage of excess weight loss (%EWL), overall complications, gastrointestinal leaks, gastroesophageal reflux disease (GERD) were pooled by meta-analysis. Stata 12.0 (Stata Corp, College Station, TX, USA) was used to perform the meta-analysis. Results: Data were extracted from 11 original studies matching our inclusion criteria. In our review, the group of patients who had operations with thinner bougies had a greater %EWL (SMD 0.23, 95% CI 0.14–0.33, P < .001) than the group where larger diameters were used. Furthermore, no significant differences were found in the incidence of overall complications (OR 1.00, 95% CI 0.73–1.37, P = .978), postoperative gastrointestinal leaks (OR 0.91, 95% CI 0.67–1.24, P = .554), and GERD (OR 0.77, 95% CI 0.37–1.59, P = .476) between the two groups. A robust result could not be made about remission of comorbidities using differing diameter bougies due to insufficient data. Conclusions: Use of thinner diameter bougies in LSG was more effective in enabling weight loss and did not increase the risk of overall complications, gastrointestinal leaks or GERD compared with larger diameter bougies. Highlights: The thinner diameter bougies had more weight loss and didn't increase the risk of postoperative complications. The development of leak is not only determined on intra-luminal pressure, but also patient selection, adjunct procedures. GERD symptoms is a temporary problem after LSG.